BLENDED TECHNIC TERAPI TASK CENTERED DAN TOKEN EKONOMI DALAM MENINGKATKAN KETERAMPILAN SOSIAL KORBAN PENYALAHGUNA NAPZA - Dameuli Paska Roma Sigalingging (DAS Institute, 2022)
Social skills are important for human life’s ability. Without having social skills, humans can not interact with other people in their environment because people really needs social skills in social life.The purpose of this research is to obtain an empirical description and analyze the characteristics of the subject, conditions of communication skills, social interaction, cooperation, motivation of the subject after receiving the Blended Technic of Therapy Task Center and Token Economy. The method used in this research is a quantitative approach with a single subject design. The technique was used of this research by using questionnaires, observations and studies documentation. The data analysis technique used in this research is quantitative data analysis technique using visual analysis under conditions. The study was conducted on subjects aged 20, 22 and 24 years. The results showed that after the intervention using Task Centered Blended Technic Therapy and Economic Tokens, the social skills of the three subjects from the initial phase (A1) showed a graph of the direction increasing up to the Outcome Phase (A2). The result shows that; Blended Technic of Therapy Task Center and Token Economy can increase social skill frequency of drugs abuser. The aspects thats increase are communicate effectively, social interaction, cooperation, and motivation skills. Blended Technic of Therapy Task Center and Token Economy are expected to help drug abusers to communicate effectively, increase social interaction, cooperate with other residents, and motivate them to carry out all the activities.